Faktor-Faktor yang Berhubungan dengan Keluhan Carpal Tunnel Syndrome (CTS) pada Pekerja di Kantor Jambi Ekspress - Nefa Repilda; Entianopa Entianopa; Eti Kurniawati (Indonesian Journal of Health Community, 2022)
Carpal Tunnel Syndrome (CTS) is a medical condition in which the central nerve is compressed in the wrist which results in numbness and muscle weakness in the hand. Workers at the Jambi Express Office work with intense computer use for 5-6 hours. so you are at risk of experiencing CTS. The research objective was to determine the factors associated with CTS. This research was a quantitative study with a cross sectional design. The research population is all workers in Jambi Ekspress as many as 41 people. The research sample was workers at Jambi Ekspress who used computers, namely as many as 30 people. As many as 36.7% of respondents experienced CTS, 76.6% of respondents worked with wrong hand posture, 100% of respondents did not make repetitive movements, 73.3% of respondents had years of service old category. The results of the bivariate analysis showed that there was a relationship between length of service (p=0.014) and CTS. There is no relationship between awkward hand postures (p = 1.000) and repetitive movements (p = 0.069) with CTS.. It is expected that workers do warm-up exercises for five minutes before starting work. Take regular breaks by bending and straightening your wrists for at least 3-5 minutes.